Surgical Outcomes of Obese Patients With Adolescent Idiopathic Scoliosis From Endemic Areas of Obesity in the United States. Issue 10 (November 2021) - McDonald, Tyler C.; Heffernan, Michael J.; Ramo, Brandon; Haber, Lawrence; Sheffer, Benjamin; Murphy, Joshua; Murphy, Robert; Fletcher, Nicholas; Coyne, Killian; Lubicky, John; Bumpass, David B.; Crawford, Charles; et al.
Abstract : Background: Obesity rates continue to rise among children and adolescents across the globe. A multicenter research consortium composed of institutions in the Southern US, located in states endemic for childhood obesity, was formed to evaluate the effect of obesity on pediatric musculoskeletal disorders. This study evaluates the effect of body mass index (BMI) percentile and socioeconomic status (SES) on surgical site infections (SSIs) and perioperative complications in patients with adolescent idiopathic scoliosis (AIS) treated with posterior spinal fusion (PSF). Methods: Eleven centers in the Southern US retrospectively reviewed postoperative AIS patients after PSF between 2011 and 2017. Each center contributed data to a centralized database from patients in the following BMI-for-age groups: normal weight (NW, 5th to <85th percentile), overweight (OW, 85th to <95th percentile), and obese (OB, ≥95th percentile). The primary outcome variable was the occurrence of an SSI. SES was measured by the Area Deprivation Index (ADI), with higher scores indicating a lower SES. Results: Seven hundred fifty-one patients were included in this study (256 NW, 235 OW, and 260 OB). OB and OW patients presented with significantly higher ADIs indicating a lower SES ( P <0.001). In addition, SSI rates were significantly different between BMI groups (0.8% NW, 4.3% OW, and 5.4% OB, P =0.012). Further analysis showed that superficial and not deep SSIs were significantly different between BMI groups. These differences in SSI rates persisted even while controlling for ADI. Wound dehiscence and readmission rates were significantly different between groups ( P =0.004 and 0.03, respectively), with OB patients demonstrating the highest rates. EBL and cell saver return were significantly higher in overweight patients ( P =0.007 and 0.002, respectively). Conclusion: OB and OW AIS patients have significantly greater superficial SSI rates than NW patients, even after controlling for SES. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.